2017
DOI: 10.1007/s00425-017-2706-8
|View full text |Cite
|
Sign up to set email alerts
|

Chondriokinesis during microsporogenesis in plants

Abstract: Main conclusion Chondriokinesis represents a highly orchestrated process of organelle rearrangement in all dividing plant and animal cells, ensuring a proper course of karyokinesis and cytokinesis. This process plays a key role in male gametophyte formation. Chondriokinesis is a regular rearrangement of cell organelles, assuring their regular inheritance, during both mitotic and meiotic divisions in plant and animal cells. The universal occurrence of the process implies its high conservatism and its probable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 103 publications
(180 reference statements)
0
21
0
Order By: Relevance
“…Ferulate 5-hydroxylase (F5H) is one of key enzymes that regulate S/G lignin composition in plants, recent study has shown that the heterologous expression of angiosperm F5H induced ectopic productions of S lignin in the gymnosperm cell walls [ 31 ]. In rice, overexpression of a F5H gene OsCAld5H1 increased the content of S units, while down-regulation of it enhanced the production of G lignin [ 32 ]. Recently, caffeoyl shikimate esterase (CSE) was reported to be involved in lignin biosynthesis in Arabidopsis thaliana , Medicago truncatula and hybrid poplar [ 33 , 34 , 35 ].…”
Section: Genetic Modification Of Lignin Biosynthesismentioning
confidence: 99%
“…Ferulate 5-hydroxylase (F5H) is one of key enzymes that regulate S/G lignin composition in plants, recent study has shown that the heterologous expression of angiosperm F5H induced ectopic productions of S lignin in the gymnosperm cell walls [ 31 ]. In rice, overexpression of a F5H gene OsCAld5H1 increased the content of S units, while down-regulation of it enhanced the production of G lignin [ 32 ]. Recently, caffeoyl shikimate esterase (CSE) was reported to be involved in lignin biosynthesis in Arabidopsis thaliana , Medicago truncatula and hybrid poplar [ 33 , 34 , 35 ].…”
Section: Genetic Modification Of Lignin Biosynthesismentioning
confidence: 99%
“…The basic role of chondriokinesis during meiosis is to ensure an even distribution of organelles between the tetrad microspores (Senjaninova 1927 ; Geneves 1967 ; Wolniak 1976 ; Dupuis 1978 ; Brown and Lemmon 1982 ; Tchórzewska 2017 ), which guarantees formation of identical, metabolically active microspores. It is believed that this process occurs with the same precision as the separation of chromosomes during karyokinesis (Geneves 1967 , 1971 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the formation, the organelles are evenly dispersed in the cytoplasm of both dyad cells. Therefore, it can be concluded that there is a close relationship between the type of chondriokinesis and the type of cytokinesis in meiosis during microsporogenesis (Bednara et al 1986 ; Tchórzewska 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations